TRADISI MAPPASIKARAWA DALAM PERNIKAHAN ADAT BUGIS DI KELURAHAN BONTONYELENG KECAMATAN GANTARANG KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study aims to see the process and meaning contained in the mappasikarawa tradition which is carried out in a Bugis traditional wedding in Bontonyeleng Village, Gantarang District, Bulukumba Regency. The focus of the research is the process and meaning of the messages contained in the mappasikarawa tradition. The results of the study indicate that the stages in the process of implementing mappasikarawa have meaning in each of the symbols used. Examination of the preparation stage, namely the necessary equipment such as air that ends in purity and betel leaf near siri' in Bugis language which means shame, the core implementation stage of the activity, begins at pappasi karawa the groom for the bride's body parts The first to be touched is the ring finger, which has a meaning (appaccicingeng) which means something valuable, always creates wealth and prosperity, then the middle finger touches (datu) which means something that is prioritized, the thumb is always close, which is filled (increased) ) weight) as a determinant of the success of a husband to make his wife happy, the base of the arm (pabbossoreng) which means mutually reinforcing one another, which in turn has a relationship that has the meaning of bitter sweetness of life that can feel and relate together and the last one has the meaning of always remembering one another. each other to always be loyal to the world and the hereafter, then the final stage saian, which indicates the procession has been completed. People think that the first touch is the most important determinant of the happiness of husband and wife after marriage. This belief and belief is what makes this tradition still carried out and preserved to this day. Furthermore, the neck has the meaning of bitter sweetness of life that can be accepted and accepted together and the last one has the meaning of always remembering each other so that they are always loyal to the world and the hereafter, the stage of completion of the settlement. which indicates the process has been completed. People think that the first touch is the most important determinant of the happiness of husband and wife after marriage. It is this belief and belief that makes this tradition still carried out and preserved today. Furthermore, the neck has the meaning of the bitter sweetness of life that can be accepted and accepted together and the last one has the meaning of always remembering each other so that they are always loyal to the world and the hereafter, the completion stage, which indicates the procession has been completed.